Analysis of Adenovirus Type 5 Early Region 1 A Insertion Mutants - Bao, Xiankun (My University, 1990)
Adenovirus Early region 1A(E1A) plays an important role in viral lytic infection and serves as a useful tool in the study of molecular mechanisms of gene regulation and gene expression. In addition to the ability of E1A functions to induce transactivation and transrepression of gene expression, E1A products play a critical role in transformation by adenovirus. A technique employing linker insertion mutagenesis scanning most of the E1A major regions was developed in this laboratory to systematically study the effect of E1A mutations on transcriptional transactivation and trans-repression functions as well as transforming ability (Bautista 1989). Results obtained showed that the unique region was the region primarily for transactivation in agreement with a wealth of other data and that transrepression was sensitive to insertions in CRII (conserved region II) and a region immediately following the unique region at the beginning of Exon II. However, transformation was not affected by repression-sensitive mutants. This thesis describes further studies carried out to create additional insertion mutants within conserved region of E1A to confirm and extend the results obtained by Bautista. A synthetic oligonucleotide of 39 base pair (13 aa) was introduced into two additional restriction sites in this region. As in previous work, the oligonucleotide could be inserted in either of two possible orientations. In one orientation, all three reading frames were open whereas all three reading frames of the other orientation contained stop codons which resulted in truncation of the E1A protein at the site of insertion. In addition, the insertion oligomer was designed with flanking BamHI sites to provide the opportunity of collapsing the full length insertion to a 6 base pair (2 aa) insertion. This allowed comparison to be made between mutations containing 13 aa insertions and those with 2 aa inserts at the same site to see how different oligopeptide segments would influence different functions. Trans-repression assays utilized a novel β-galactosidase assay developed by Bautista for characterizing CRII mutants expressing only the 12S product. The results suggested that CRII was an important region in terms of ability of E1A to transrepress. This negative regulatory function was sensitive to full length 13 aa insertions but not 2 aa inserts for those mutants made to date. Transforming ability of all CRII mutants was more or less impaired. Transactivation activity was not reduced by insertion at CRII except for mutants which were in the reverse orientation and had stop codons in their reading frame thus terminating the translation upstream of the unique region. In an effort to identify functional temperature sensitive mutants, DNA-mediated transformation assays of mutants within E1A functional regions were carried out at different temperatures. Two transformation temperature sensitive mutants were identified which failed to produce transformed colonies at 38.5°C but transformed efficiently at 32°C. No replication temperature sensitive mutants were identified among 61 mutant viruses.
Keywords: adenovirus; mutant; insertion